Legal Certainty of Biometric-Based Electronic Contracts under Indonesian Contract Law - Rahmawati Sabila; Wiwin Widiyaningsih; Zuraidah (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
The development of information technology has encouraged the extensive use of electronic contracts, including the application of biometric methods as mechanisms for authentication and consent. Although biometrics provide efficiency and enhanced security, their use in electronic contracts raises legal issues concerning contractual validity and legal certainty. This study aims to analyze the legal certainty of biometric-based electronic contracts in relation to Article 1320 of the Indonesian Civil Code and the Law on Information and Electronic Transactions (ITE Law). This research employs a normative legal research method using statutory and conceptual approaches, supported by library-based analysis of relevant legal materials. The findings indicate that biometric-based electronic contracts may, in principle, be considered legally valid provided that the legal requirements for a valid contract particularly mutual consent are fulfilled. However, legal certainty remains limited due to the absence of explicit regulation governing the legal status of biometrics as a form of electronic authentication or electronic signature, as well as challenges related to the protection of biometric data as sensitive personal data. This study contributes by identifying normative gaps in the regulation of biometric authentication and proposing regulatory harmonization to enhance legal certainty and personal data protection